PNUTS forms a trimeric protein complex with GABAC receptors and protein phosphatase 1. - Rose, Melanie; Dütting, Eva; Schröder, Nadja; Sticht, Heinrich; Brandstätter, Johann Helmut; Enz, Ralf (Molecular and Cellular Neuroscience, 2008)
Phosphorylation and dephosphorylation of neurotransmitter receptors represent an important mechanism to regulate synaptic signal transduction. Here, we identified PNUTS, a targeting subunit of protein phosphatase 1 (PP1) as a new binding partner of GABAC receptors. In the mammalian retina, PNUTS is co-expressed with GABAC receptors and PP1 in bipolar cells. PNUTS and PP1 were detected in membrane protein preparations of the retina and precipitate with GABAC receptor specific antibodies. Furthermore, PNUTS shuttles from the nucleus to the membrane in cells co-expressing GABAC receptors. We show simultaneous binding of PP1 and GABAC receptors to different domains of PNUTS, demonstrating that PNUTS cross-links PP1 and GABAC receptors. Finally, modeling studies showed that the PP1 docking motif of PNUTS fits into the binding pocket on the enzyme surface, despite a C-terminal adjacent proline. We suggest that PNUTS targets PP1 to synaptic sites, acting as a temporary bridge between the phosphatase and GABAC receptors. © 2007 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2008.med.IB.profes_1.pnutsf_1
Keywords: Docking motif; GABA receptor; PP1C; Protein interaction; Retina; rho subunit

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation - Pieger, Katharina; Schmitt, Verena; Gauer, Carina; Gießl, Nadja; Prots, Iryna; Winner, Beate; Winkler, Jürgen; Brandstätter, Johann Helmut; Xiang, Wei (Biomolecules, 2022)
Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson's disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffinity towards aSyn in the nucleus. Comparing the Nu-aSyn-C antibody to aSyn antibodies developed against phosphorylated or aggregated forms, we observed that nuclear aSyn differs from cytosolic aSyn by an increased phosphorylation and assembly level in proliferating cells. Employing Nu-aSyn-C, we characterized aSyn distribution during neuronal differentiation in midbrain dopaminergic neurons (mDANs) derived from human-induced pluripotent stem cells (hiPSCs) and Lund human mesencephalic cells, and in primary rat hippocampal neurons. We detected a specific translocation pattern of aSyn during neuronal differentiation from the nucleus to the soma and finally to neuronal processes. Interestingly, a remarkable shift of Nu-aSyn-C-positive species towards neurites was detected in hiPSC mDANs from a PD patient carrying aSyn gene duplication. Together, our results reveal distinct nuclear and cytosolic aSyn species that redistribute during neuronal differentiation-a process that is altered in PD-derived neurons.
CRIS-Team WoS Importer:2022-09-09